국내 거주 중국인 유학생의 치과의료 이용 실태조사 - 김선주; Sun Ju Kim; 황수현; Su Hyun Hwang; 유지수; Ji Su Yu (Chiwisaeng gwahakoeji, 2011)
The purpose of this study was to examine the use of dental institutions among Chinese students in Korea in an attempt to provide some information on how to make more and better dental services accessible to them. The subjects in this study were Chinese students who were studying in eight different colleges. After a survey was conducted from April 1 to July 15, 2011, the following findings were given: 1. Concerning experiences of using domestic dental institutions, the majority of the respondents never received dental treatment in our country. The most widely used dental institutions were dental clinics, and the most common treatment they received was about dental caries. 2. As for the reason why they didn`t receive dental treatment in our country, the biggest group cited the burden of medical cost and time constraints as the reasons. 3. The students who had medical insurance slightly outnumbered those who hadn`t. Regarding the necessity of medical insurance, most of them considered that to be necessary, and those who had medical insurance received more dental treatment than the others who hadn`t. 4. As to satisfaction with dental treatment, the students who were better at Korean expressed more satisfaction, and those who had medical insurance were better satisfied than the others who hadn`t. In conclusion, the medical insurance system should be improved to let Chinese students have medical insurance compulsorily to ensure their efficient use of dental institutions, and every college should offer administrative assistance for health care.